Front slurry for TOPCon battery and preparation method and application thereof
By using large and small particles of silver powder, lead-free glass powder, silver bismuth acid and silver tellurate in the front slurry of TOPCon battery, an efficient silver grain conductive dielectric is formed, which solves the acetic acid corrosion of the battery in high temperature and high humidity environments. The problem is that it improves acid resistance and photoelectric conversion efficiency, is suitable for single glass components and reduces environmental pollution.
Patent Information
- Application Number
- CN202411165608.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
AI Technical Summary
TOPCon batteries are susceptible to acetic acid corrosion in high temperature and high humidity environments, resulting in power attenuation of photovoltaic modules. The existing glass powder has insufficient acid resistance, which affects the reliability and environmental friendliness of single glass modules.
Using a combination of large and small-grain silver powder, two lead-free glass powder systems, as well as silver bismuth acid and silver tellurate as inorganic additives, the acid resistance and conductivity of the slurry are improved through specific preparation methods to form efficient silver crystals. Particle conductive dielectric.
It significantly improves the resistance of the electrodes, reduces resistance, enhances the photoelectric conversion efficiency, meets the requirements of single glass components, and lead-free glass powder reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of crystalline silicon solar cells, and in particular relates to a front slurry for a TOPCon cell and a preparation method and application thereof. Background Art
[0002] Due to the advantages of high battery efficiency, low temperature coefficient, and low light decay, n-type TOPCon batteries have developed rapidly in the past two years, and their market share has continued to rise. When TOPCon batteries are packaged, double-glass packaging is usually used to pass relevant reliability tests, especially damp heat tests. The main reason is that when the components are placed in a high temperature and high humidity environment for a long time, the encapsulation film EVA will decompose and release acetic acid, which will corrode the battery electrodes, affect the conversion efficiency of the photovoltaic components, and cause the components to produce significant power attenuation. Double-glass components can effectively block the generation of water vapor, thereby ensuring the reliability of the components. However, double-glass components are heavy and inconvenient to transport and install. Single-glass components are light in weight, which can save manpower, transportation and other system costs. They are particularly suitable for installation in sites with high weight requirements, but single-glass components have high requirements for the battery's resistance to acetic acid corrosion.
[0003] In order to make single-glass modules, the battery electrodes, especially the front electrodes, must have high resistance to acetic acid. The front electrode is formed by screen printing of the front silver paste. The front paste is usually composed of silver powder, glass powder and organic carrier, among which glass is the key component affecting the paste's resistance to acetic acid. At present, the glass of the existing system is glass with a high PbO content. Lead oxide easily reacts with acetic acid to form lead acetate, which has poor acid resistance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a front slurry for TOPCon batteries with high acid resistance and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0006] A front paste for a TOPCon battery comprises, by mass percentage, 86-92wt% of silver powder, 1.5-5.5wt% of glass powder, 5-10wt% of an organic carrier, and 1-3wt% of an inorganic additive, wherein the silver powder comprises large-particle silver powder and small-particle silver powder.
[0007] In the above-mentioned positive paste for TOPCon battery, preferably, the large-particle silver powder accounts for 60-90wt% of the total mass of the silver powder, the particle size D50 of the large-particle silver powder is 1-2μm, D100 is less than 5μm, and the specific surface area is 0.3-0.7g / cm 3 .
[0008] In the above-mentioned positive paste for TOPCon battery, preferably, the small-particle silver powder accounts for 10-40wt% of the total mass of the silver powder, the particle size D50 of the small-particle silver powder is 0.1-0.8μm, D100 is less than 3μm, and the specific surface area is 0.5-0.9g / cm 3 .
[0009] In the above-mentioned front paste for TOPCon battery, preferably, the glass powder includes main glass powder and auxiliary glass powder, the main glass powder accounts for 50-80wt% of the total mass of the glass powder, and the auxiliary glass powder accounts for 20-50% of the total mass of the glass powder.
[0010] The above-mentioned front paste for TOPCon battery, preferably, based on the mass content of the components of the glass powder, the main glass powder includes 20-45wt% Bi2O3, 10-35wt% SiO2, and 20-45wt% ZnO.
[0011] In the above-mentioned front paste for TOPCon battery, preferably, the main glass powder also includes one or more of La2O3, CeO2, WO3, and MoO3, and the addition amount thereof is 1-5wt%.
[0012] The above-mentioned front paste for TOPCon battery, preferably, based on the mass content of the components of the glass powder, the secondary glass powder includes 30-50wt% B2O3, 20-40wt% SiO2, 5-10wt% Al2O3 and 10-20wt% alkaline earth metal oxide, wherein the alkaline earth metal oxide is selected from one or more of MgO, CaO, and BaO.
[0013] In the front paste for the TOPCon battery, the inorganic additive is preferably one or more of silver bismuthate and silver tellurate. Silver bismuthate and silver tellurate are silver salt oxides that can decompose and release oxygen at high temperatures. The function of the additive is to release oxygen at high temperatures, promote the reaction between the glass and the silicon substrate, and quickly generate the silver grain conductive medium at the temperature of the paste sintering, thereby ensuring the formation of ohmic contact and reducing the damage of the paste to the silicon substrate.
[0014] The above-mentioned TOPCon battery front slurry, preferably, the organic carrier is prepared by the following preparation method: solvent butyl carbitol, butyl carbitol acetate, alcohol ester dodecahydrate, silicone oil, ethyl cellulose and thixotropic agent polyamide wax are mixed, activated at 50-70°C for 1-2h, and cooled to room temperature to obtain the organic carrier.
[0015] In the above-mentioned TOPCon battery front slurry, preferably, the glass powder is prepared by the following preparation method:
[0016] (1) According to the composition of the glass powder, the oxides are fully mixed;
[0017] (2) transferring the mixture obtained in step (1) to a platinum crucible, placing it in a high-temperature furnace and heating it at a temperature of 1000-1200° C. for a holding time of 20-60 min;
[0018] (3) The high-temperature melt after heating and heat preservation in step (2) is quickly poured into deionized water for rapid cooling to obtain glass slag, and finally the glass slag is ball-milled in a ball mill to obtain glass powder.
[0019] Based on a general inventive concept, the present invention also provides a method for preparing the above-mentioned front slurry for TOPCon batteries, wherein silver powder, glass powder, organic carrier and inorganic additive are weighed according to the mass ratio and mixed, and then ground with a three-roll grinder until the fineness of the slurry is less than 5 μm, thereby obtaining the front slurry for TOPCon batteries.
[0020] Based on a general inventive concept, the present invention also provides an application of the above-mentioned front slurry for TOPCon battery in a TOPCon battery.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the front paste for TOPCon batteries of the present invention, two silver powders of different specifications are used, with large-particle silver powder as the main component and small-particle silver powder as the auxiliary component. The small-particle silver powder can be filled in the pores of the large-particle silver powder, thereby reducing the porosity of the sintered silver powder, improving the density of the sintered silver powder, and reducing the electrode resistance. At the same time, the area of the electrode after sintering that is corroded by acetic acid is reduced, thereby enhancing the electrode's resistance to acetic acid corrosion.
[0023] (2) In the front paste for TOPCon batteries of the present invention, two types of glass powder are used, both of which are lead-free glass powder. The lead-free glass powder can further increase the ability of the electrode to resist acetic acid corrosion; and the lead-free glass powder can reduce environmental pollution and is more environmentally friendly.
[0024] (3) In the front paste for TOPCon cells of the present invention, two different glass systems are used: bismuth oxide-based main glass powder and boron oxide-based auxiliary glass powder, which control the fluidity of the glass at different stages and its corrosiveness to the silicon substrate. The bismuth oxide-based main glass powder is easy to react with silicon nitride to etch the silicon nitride anti-reflection film; the boron oxide-based auxiliary glass powder is easy to form a low-melting compound with aluminum oxide, thereby corroding through the aluminum oxide dielectric layer, ensuring the contact between the electrode and the silicon emitter, so that a good ohmic contact can be formed after sintering; at the same time, the glass transition temperature of the two different glasses is controlled to maintain balanced corrosion of the silicon nitride and aluminum oxide dielectric layers, reducing the damage area to the silicon emitter, thereby ensuring the opening voltage.
[0025] (4) Silver bismuthate and silver tellurate are added to the front paste for TOPCon batteries of the present invention. Silver salt oxides such as silver bismuthate and silver tellurate that can decompose at high temperatures and release oxygen are used. The role of using silver bismuthate and silver tellurate additives is to release oxygen when decomposed at high temperatures, promote the formation of silver grains during sintering, so that silver grains can be generated in the effective area opened in the dielectric layer, increase the conductive path during current transmission, and reduce the contact resistivity.
[0026] (5) The TOPCon cell using the front slurry for the TOPCon cell of the present invention can obtain higher photoelectric conversion efficiency and better resistance to acetic acid, thereby meeting the requirements for single-glass components. DETAILED DESCRIPTION
[0027] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0028] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0030] The raw material ratios of the main and auxiliary glass powders in the following embodiments are shown in Tables 1 and 2, and the composition and content of the front slurry for TOPCon cells are shown in Table 3.
[0031] Table 1 Main glass powder formula (wt.%) in the embodiment
[0032] Glass No. <![CDATA[Bi2O3]]> <![CDATA[SiO2]]> ZnO <![CDATA[WO3]]> <![CDATA[MoO3]]> G1-1 20 32 45 3 G1-2 45 10 43 2 G1-3 44 35 20 1 G1-4 40 25 30 2 3
[0033] Table 2: Secondary glass powder formulation in the embodiment (wt.%)
[0034] Glass No. <![CDATA[B2O3]]> <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO CaO G2-1 30 40 10 20 G2-2 50 20 10 10 10 G2-3 40 40 10 10 G2-4 45 35 5 15
[0035] Table 3 Slurry composition and content in the examples
[0036] Slurry No. Large particle silver powder Small silver powder Main glass powder G1 Secondary glass powder G2 Organic carrier Inorganic additives P1 77.4 8.6 4.4 1.1 7.5 1 P2 55.2 36.8 0.75 0.75 5 1.5 P3 69.6 17.4 1.8 1.2 7 3 P4 69.6 17.4 0.9 0.6 10 1.5 P5 72 18 1.2 0.8 7 1 P6 90 / 1.2 0.8 7 1 P7 72 18 2 / 7 1 P8 72 18 2 / 7 1 P9 72 18 1.2 0.8 8 /
[0037] The organic carrier involved in the following embodiments is prepared by the following preparation method:
[0038] (1) Weigh the components in proportion, with a total amount of 100 g, including 40 g of butyl carbitol solvent, 45 g of butyl carbitol acetate, 5 g of alcohol ester dodecahydrate, 3 g of silicone oil, 5 g of ethyl cellulose and 2 g of thixotropic agent polyamide wax;
[0039] (2) stirring the substances weighed in step (1) using a stirrer, and then activating the mixture at 60° C. for 2 hours;
[0040] (3) Cool the activated carrier to room temperature for later use.
[0041] Embodiment 1:
[0042] The method for preparing the glass powder involved in this embodiment comprises the following steps:
[0043] (1) Weigh the glass component oxides according to the ratio of G1-1 in Table 1 or G2-1 in Table 2, with a total weight of 100 g, and mix them evenly;
[0044] (2) The mixture was transferred into a platinum crucible, and the platinum crucible was placed in a high-temperature resistance furnace and heated at 1000° C. for 60 min.
[0045] (3) After the holding time is reached, the high-temperature glass melt is quickly poured into deionized water for rapid cooling, and the obtained glass slag is ball-milled and dried to obtain the corresponding glass powder.
[0046] The front slurry used for N-type crystalline silicon TOPCon cells in this embodiment is prepared as follows:
[0047] (1) Select large-particle silver powder and small-particle silver powder. The large-particle silver powder has a D50 of 2 μm and a specific surface area of 0.3 g / cm 3 , small particle silver powder D50 is 0.8μm, specific surface area is 0.5g / cm 3 .
[0048] (2) Weigh large-particle silver powder, small-particle silver powder, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver bismuthate according to the proportion shown in P1 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P1.
[0049] Embodiment 2:
[0050] The method for preparing the glass powder involved in this embodiment comprises the following steps:
[0051] (1) Weigh the glass component oxides according to the ratio of G1-2 in Table 1 or G2-2 in Table 2, with a total weight of 100 g, and mix them evenly;
[0052] (2) The mixture was transferred into a platinum crucible, and the platinum crucible was placed in a high-temperature resistance furnace and heated at 1200° C. for 20 min.
[0053] (3) After the holding time is reached, the high-temperature glass melt is quickly poured into deionized water for rapid cooling, and the obtained glass slag is ball-milled and dried to obtain the corresponding glass powder.
[0054] The front slurry used for N-type crystalline silicon TOPCon cells in this embodiment is prepared as follows:
[0055] (1) Select large-particle silver powder and small-particle silver powder. The large-particle silver powder has a D50 of 1 μm and a specific surface area of 0.7 g / cm 3 , small particle silver powder D50 is 0.1μm, specific surface area is 0.9g / cm 3 .
[0056] (2) Weigh large silver powder particles, small silver powder particles, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver bismuthate according to the proportion shown in P2 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P2.
[0057] Embodiment 3:
[0058] The formula of the main glass powder in this embodiment is shown in G1-3 in Table 1 and the formula of the auxiliary glass powder is shown in G2-3 in Table 2. The specific preparation method is the same as that in Example 2.
[0059] The front slurry used for N-type crystalline silicon TOPCon cells in this embodiment is prepared as follows:
[0060] (1) Selecting large-particle silver powder and small-particle silver powder, as in Example 2;
[0061] (2) Weigh large silver powder particles, small silver powder particles, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver bismuthate according to the proportion shown in P3 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P3.
[0062] Embodiment 4:
[0063] The formula of the main glass powder in this embodiment is shown in G1-4 in Table 1 and the formula of the auxiliary glass powder is shown in G2-4 in Table 2. The specific preparation method is the same as that in Example 2.
[0064] The front slurry used for N-type crystalline silicon TOPCon cells in this embodiment is prepared as follows:
[0065] (1) Select large-particle silver powder and small-particle silver powder. The D50 of the large-particle silver powder is 1 μm and the specific surface area is 0.7 g / cm 3 The specification of small-particle silver powder is D50 300nm and the specific surface area is 0.8g / cm 3 ;
[0066] (2) Weigh large-particle silver powder, small-particle silver powder, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver bismuthate according to the proportion shown in P4 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P4.
[0067] Embodiment 5:
[0068] The formula of the main glass powder in this embodiment is shown in G1-4 in Table 1 and the formula of the auxiliary glass powder is shown in G2-4 in Table 2. The specific preparation method is the same as that in Example 2.
[0069] The front slurry used for N-type crystalline silicon TOPCon cells in this embodiment is prepared as follows:
[0070] (1) Selecting large-particle silver powder and small-particle silver powder, as in Example 4;
[0071] (2) Weigh large-particle silver powder, small-particle silver powder, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver tellurate according to the proportion shown in P5 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P5.
[0072] Comparative Example 1:
[0073] The formula of the main glass powder in this comparative example is shown in G1-4 in Table 1, and the formula of the auxiliary glass powder is shown in G2-4 in Table 2. The specific preparation method is the same as that in Example 2.
[0074] The preparation process of the front silver paste applied to the N-type crystalline silicon TOPCon cell in this comparative example is as follows:
[0075] (1) Select silver powder with a D50 of 1 μm and a specific surface area of 0.7 g / cm 3 ;
[0076] (2) Silver powder, main glass powder, auxiliary glass powder, organic carrier and inorganic additive silver tellurate are weighed according to the proportion shown in P6 in Table 3, and fully stirred, and then ground with a three-roll grinder until the fineness of the slurry is less than 5μm to obtain a front slurry, which is numbered P6.
[0077] Comparative Example 2:
[0078] The formula of the glass powder in this comparative example is shown in G1-4 in Table 1, and the specific preparation method is the same as that in Example 2.
[0079] The preparation process of the front silver paste applied to the N-type crystalline silicon TOPCon cell in this comparative example is as follows:
[0080] (1) Selecting large-particle silver powder and small-particle silver powder, as in Example 4;
[0081] (2) Weigh large-particle silver powder, small-particle silver powder, glass powder, organic carrier and inorganic additive silver tellurate according to the proportion shown in P7 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P7.
[0082] Comparative Example 3:
[0083] In this comparative example, lead-containing glass is used as a control, and its composition includes PbO: 40%, B2O3: 30%, SiO2: 10%, ZnO: 10%, and TiO2: 10%. Its preparation method is the same as that in Example 2.
[0084] The preparation process of the front silver paste applied to the N-type crystalline silicon TOPCon cell in this comparative example is as follows:
[0085] (1) Selecting large-particle silver powder and small-particle silver powder, as in Example 4;
[0086] (2) Weigh large-particle silver powder, small-particle silver powder, glass powder, organic carrier and inorganic additive silver tellurate according to the proportion shown in P8 in Table 3, stir them thoroughly, and then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P8.
[0087] Comparative Example 4:
[0088] The formula of the main glass powder in this comparative example is shown in G1-4 in Table 1, and the formula of the auxiliary glass powder is shown in G2-4 in Table 2. The specific preparation method is the same as that in Example 2.
[0089] The preparation process of the front silver paste applied to the N-type crystalline silicon TOPCon cell in this comparative example is as follows:
[0090] (1) Selecting large-particle silver powder and small-particle silver powder, as in Example 4;
[0091] (2) Weigh large-particle silver powder, small-particle silver powder, main glass powder, auxiliary glass powder, and organic carrier according to the proportion shown in P9 in Table 3, and stir them thoroughly. Then grind them with a three-roll grinder until the fineness of the slurry is less than 5 μm to obtain a front slurry, which is numbered P9.
[0092] The front slurry prepared in Examples 1-5 and Comparative Examples 1-4 was printed and sintered, and laser irradiated by the LECO process to complete the electrode contact formation. The IV performance and acetic acid resistance of the battery cell were tested, wherein the test method for acetic acid resistance was: the battery cell was subjected to IV and EL tests, and then placed in an acetic acid box for experiment, the temperature was 85°C, the concentration of acetic acid saturated solution was 3%, the experiment time was 8 hours, and the IV performance was tested after the experiment, and the attenuation rate after acetic acid was calculated, that is, the difference in conversion efficiency before and after acetic acid divided by the efficiency before acetic acid. The open circuit voltage (Voc), short circuit current (Isc), fill factor (FF), series resistance (Rs), parallel resistance (Rsh) data and acetic acid attenuation were detected, and the results are shown in Table 4.
[0093] Table 4 IV electrical properties and acetic acid attenuation data of P1-P9 slurries
[0094] Slurry No. Eta(%) <![CDATA[V oc (mV)]]> <![CDATA[I sc (mA)]]> FF(%) <![CDATA[R sh (Oh)]]> <![CDATA[R s (mΩ)]]> Acetic acid decay rate (%) P1 26.27 0.7337 13.977 85.31 1647 0.142 15 P2 26.22 0.7328 14.006 85.07 1124 0.126 12 P3 26.21 0.7338 14.017 84.87 1231 0.135 18 P4 26.24 0.7335 14.002 85.08 1440 0.117 12 P5 26.23 0.7323 14.001 85.20 1248 0.119 14 P6 26.08 0.7318 14.008 84.74 1524 0.238 30 P7 26.08 0.7330 14.009 84.58 1056 0.223 15 P8 26.21 0.7338 14.011 84.90 1310 0.149 35 P9 26.13 0.7320 13.992 84.96 1136 0.162 12
[0095] It can be seen from Table 4 that the slurries P1-P5 prepared in Examples 1-5 can obtain higher photoelectric conversion efficiency and good acetic acid resistance after silk screen sintering, which means that the slurry can form good ohmic contact between silver and silicon after sintering, and the sintering causes less damage to the polycrystalline, the metallization composite is lower, and the ability to resist acetic acid corrosion is stronger.
[0096] In Comparative Example 1, since the slurry contains only one type of silver powder, the electrode porosity formed after sintering is relatively high, resulting in increased line resistance. The high porosity also leads to an increase in the acetic acid corrosion area, and the electrical properties and acetic acid resistance are relatively poor.
[0097] In Comparative Example 2, since the slurry contains only one lead-free glass powder, the glass powder does not corrode the dielectric layer properly, resulting in high contact resistance, decreased battery FF, and reduced conversion efficiency.
[0098] In Comparative Example 3, since the slurry contains lead oxide glass powder, lead oxide easily reacts with acetic acid to form lead acetate, which causes the glass layer between the electrode and silicon to be corroded by the acetic acid, thereby increasing the contact resistance and having poor acetic acid resistance.
[0099] In Comparative Example 4, since no inorganic additives are added, no additional oxygen is provided during sintering, and the oxygen supply required to generate silver grains is insufficient, resulting in fewer silver grains, which leads to increased contact resistance, poor filling, and thus low conversion efficiency.
Claims
1. A front slurry for TOPCon cells, It is characterized in that Calculated by mass percentage, the invention comprises 86-92wt% of silver powder, 1.5-5.5wt% of glass powder, 5-10wt% of organic carrier and 1-3wt% of inorganic additive, wherein the silver powder comprises large-particle silver powder and small-particle silver powder.
2. The front slurry for TOPCon battery according to claim 1, It is characterized in that The large-particle silver powder accounts for 60-90wt% of the total weight of the silver powder, and the particle size D50 of the large-particle silver powder is 1-2μm, and the specific surface area is 0.3-0.7g / cm 3 .
3. The front slurry for TOPCon battery according to claim 1, It is characterized in that The small silver powder particles account for 10-40 wt% of the total weight of the silver powder, the particle size D50 of the small silver powder particles is 0.1-0.8 μm, and the specific surface area is 0.5-0.9 g / cm 3 .
4. The front slurry for TOPCon battery according to claim 1, It is characterized in that The glass powder comprises a main glass powder and a secondary glass powder, wherein the main glass powder accounts for 50-80wt% of the total mass of the glass powder, and the secondary glass powder accounts for 20-50% of the total mass of the glass powder.
5. The front slurry for TOPCon battery according to claim 4, It is characterized in that According to the mass content of the components of the glass powder, the main glass powder includes 20-45wt% Bi 2 O 3 、10-35wt%SiO 2 , 20-45wt% ZnO.
6. The front slurry for TOPCon battery according to claim 5, It is characterized in that The main glass powder also includes La 2 O 3 、CeO 2 , WO 3 、MoO 3 One or more of the above, the addition amount is 1-5wt%.
7. The front slurry for TOPCon battery according to claim 4, It is characterized in that According to the mass content of the glass powder components, the auxiliary glass powder includes 30-50wt% B 2 O 3 , 20-40wt%SiO 2 、5-10wt%Al 2 O 3 and 10-20wt% of alkaline earth metal oxide, wherein the alkaline earth metal oxide is selected from one or more of MgO, CaO and BaO.
8. The front slurry for TOPCon battery according to any one of claims 1 to 7, It is characterized in that The inorganic additive is one or more of silver bismuthate and silver tellurate.
9. A method for preparing a front slurry for a TOPCon battery as claimed in any one of claims 1 to 8, It is characterized in that According to the mass ratio, silver powder, glass powder, organic carrier and inorganic additive are weighed and mixed, and then ground with a three-roll grinder until the fineness of the slurry is less than 5 μm, thereby obtaining the front slurry for the TOPCon battery.
10. Use of the front slurry for TOPCon battery as claimed in any one of claims 1 to 8 in a TOPCon battery.
